Mongolia Central Economic Corridor Assessment : A Value Chain Analysis of Wool-Cashmere, Meat and Leather Industries - World Bank Group (World Bank, Washington, DC, 2019)
Mongolia has a comparative advantage in agribusiness, especially downstream industries using livestock products. Yet its share in worldwide exports of agribusiness commodities is insignificant. Enhancing the efficiency of the central economic corridor (CEC) is vital to Mongolia’s effort to improve trade competitiveness and diversify exports. The role of Mongolia’s economic corridors is best understood when seen as an integral part of the country’s supply chain. The report analyzes the performance gap of the CEC through an examination of three sectors: (a) cashmere and wool sector, (b) meat, and (c) leather. These sectors highlight the major challenges that Mongolian producers face in a world where agribusiness depends on a demanding retail sector characterized by tight delivery schedules and high-quality standards, which are more important than tariffs. The report diagnoses the challenges that these industries face, identifies opportunities for the growth of these sectors, leveraging the potential of the CEC, and shares policy recommendations on how to seize these opportunities. The analysis shows that Mongolia’s comparative advantage has been significantly diluted by weaknesses associated with its economic corridors.